2014
DOI: 10.1016/j.bbagen.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the Staphylococcus aureus bacillithiol transferase BstA

Abstract: Background Gram-positive bacteria in the phylum Firmicutes synthesize the low molecular weight thiol bacillithiol rather than glutathione or mycothiol. The bacillithiol transferase YfiT from Bacillus subtilis was identified as a new member of the recently discovered DinB/YfiT-like Superfamily. Based on structural similarity using the Superfamily program, we have determined 30 of 31 Staphylococcus aureus strains encode a single bacillithiol transferase from the DinB/YfiT-like Superfamily, while the remaining st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 44 publications
(80 reference statements)
0
34
0
Order By: Relevance
“…The native substrates for two mycothiol-dependent enzymes from the S -transferase like (STL) superfamily [52], formerly known as the DinB/YfiT-like superfamily, have been characterized from Actinomycetes. Corynebacterium glutamicum was found to grow on aromatic hydrocarbons like gentisate as a sole carbon source in a mycothiol-dependent manner.…”
Section: Identification Of Bacillithiol-dependent and Bacillithiol-relamentioning
confidence: 99%
See 4 more Smart Citations
“…The native substrates for two mycothiol-dependent enzymes from the S -transferase like (STL) superfamily [52], formerly known as the DinB/YfiT-like superfamily, have been characterized from Actinomycetes. Corynebacterium glutamicum was found to grow on aromatic hydrocarbons like gentisate as a sole carbon source in a mycothiol-dependent manner.…”
Section: Identification Of Bacillithiol-dependent and Bacillithiol-relamentioning
confidence: 99%
“…The single predicted S. aureus Newman STL enzyme (ORF ID NWMN_2591) was identified in a Superfamily search (http://supfam.org/SUPERFAMILY/) using B. subtilis BstA as a query sequence against the S. aureus Newman genome. The S. aureus enzyme was confirmed to be a bacillithiol transferase on the basis of biochemical studies of cell free extracts [22] and the purified protein and was named S. aureus BstA [52]. Kinetic studies with S. aureus BstA demonstrated that the K m for BSH is 16 ± 4 µM, which is ~10-fold lower than the intracellular concentration of bacillithiol in S. aureus , indicating that the enzyme is saturated with bacillithiol in vivo [52].…”
Section: Identification Of Bacillithiol-dependent and Bacillithiol-relamentioning
confidence: 99%
See 3 more Smart Citations